Sexual Violence Among Youth in New Mexico: Risk and Resiliency Factors That Impact Behavioral Health Outcomes. Issue 2 (April 2016) - Reed, Danielle; Reno, Jessica; Green, Dan
Abstract : Research has consistently demonstrated a relationship between history of forced sex and poor behavioral health outcomes. The objectives of this study were to describe this relationship among high school students and to explore the impact of resiliency factors. Using data from the 2013 New Mexico Youth Risk and Resiliency Survey, we found that history of forced sex was associated with negative behavioral health outcomes for males and females, regardless of sexual orientation and disability status. Furthermore, the presence of a caring adult at home appeared to reduce the risk of substance abuse and suicidality among students with and without a history of forced sex.